(untitled) (Research, Society and Development, 2021)
The objective was to identify the level of knowledge of undergraduate medical students at a university in Santa Catarina about the Unified Health System (UHS). The research was carried out with students from the first to the sixth year who answered a questionnaire, which was divided into two parts: the first, related to the interviewee’s socioeconomic information; and the second, with data that aim to evaluate the student’s knowledge about UHS, emphasizing the importance of this learning during graduation. From the survey obtained on the degree of importance they attributed to knowledge about UHS, one (1.7%) academic considered this to be unimportant, 18 (30%) as important and 40 (66.7%) as very important. In addition, 51 (85%) students stated that they intended to work at UHS after the end of the university; and nine (15%) did not. Understanding UHS is essential as it offers all Brazilian citizens full, universal and free access to health services and is one of the largest and best public health systems in the world, benefiting care, from simple outpatient procedures to highly complex care, such as organ transplants.